2014
DOI: 10.1038/cgt.2014.41
|View full text |Cite
|
Sign up to set email alerts
|

The role of testicular nuclear receptor 4 in chemo-resistance of docetaxel in castration-resistant prostate cancer

Abstract: Docetaxel-based therapy is one of the first-line options for castration-resistant prostate cancer (CRPC). However, a large proportion of CRPC patients show different extents of docetaxel resistance. The current study aims to investigate the role of testicular nuclear receptor 4 (TR4) in docetaxel resistance in CRPC. TR4 expression level in prostate biopsy samples from CRPC patients treated with docetaxel was measured by immunohistochemistry (IHC). Alternation of TR4 expression in prostate cancer (PCa) cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…(2) BRN5, a pou domain TF of which very little is known, and (3) TR2 and TR4; members of the orphan nuclear receptor family, for which activation or deactivation involves an intricate interplay of different structural classes of endogenous ligands such as the heterodimeric receptors that partner with the retinoid X receptor and bind retinoids and vitamin D [ 35 ]. In support of our findings, in recent months Chen et al demonstrated that TR4 enhances the chemo-resistance of docetaxel in CRPC, and that it may serve as a biomarker to determine the prognosis of docetaxel-based therapy [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…(2) BRN5, a pou domain TF of which very little is known, and (3) TR2 and TR4; members of the orphan nuclear receptor family, for which activation or deactivation involves an intricate interplay of different structural classes of endogenous ligands such as the heterodimeric receptors that partner with the retinoid X receptor and bind retinoids and vitamin D [ 35 ]. In support of our findings, in recent months Chen et al demonstrated that TR4 enhances the chemo-resistance of docetaxel in CRPC, and that it may serve as a biomarker to determine the prognosis of docetaxel-based therapy [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…[4][5][6] Earlier studies from TR4 knockout (TR4KO) mice revealed that TR4 might play important roles in fertility, bone formation, neural development and metabolism. [7][8][9][10][11] Recent studies also found TR4 might play a negative role to suppress prostate cancer (PCa) initiation, yet played a positive role to promote PCa metastasis, [12][13][14] which is opposite the androgen receptor that promotes PCa initiation and suppresses PCa metastases. 15 These contrasting results prompted us to investigate TR4 potential impacts on the ccRCC progression.…”
mentioning
confidence: 99%
“…Extraction of total RNA and synthesize of cDNA was performed as described previously . Quantitative real‐time PCR was performed using the TIANGEN® Real Master Mix (SYBR Green) and ABI 7500 real‐time PCR system (Applied Bio‐Systems, USA).…”
Section: Methodsmentioning
confidence: 99%
“…GAPDH served as an internal control. The primers of TR4 and GAPDH were designed as described respectively : TR4 forward (5′‐ggctctgaacctgcctctg‐3′), TR4 reverse (5′‐aggatgaactgctgtttggg‐3′), GAPDH forward (5′‐ggagtcaacggatttggt‐3′), and GAPDH reverse (5′‐gtgatgggatttccattgat‐3′). The reaction conditions were 95°C 2 min, followed by 40 cycles of 95°C 30 sec, 60°C 30 sec, 68°C 1 min, with a final extension at 72°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation